Ciara Bell: capstone - Bell, Ciara, artist (Colorado State University. Libraries, 2015)
The artist's statement: I love informative, creative design and I believe that art and design are important means of communication that have the ability to cross cultural and language barriers. I like to use design to help a cause, or educate the public. The unusual and wonderful aspects of nature and humanity inspire me my work. Design and media have the potential to make a positive impact on the viewer, and I strive to make my work do so. I want my designs to reach a global audience and impact both visually and with valuable content. I think that if people can learn something about themselves or the world than I am doing my job as a graphic designer and communicator.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design